Retail Experience Design - Adding Value via Systematic Experience Design in Retailing - Joachim Hurth; Jörn Redler (Marketing Review St.Gallen, 2018)
Today, experience design is a main lever to create added value for the customer. Especially in highly competitive environments like the retailing industry it is seen as pivotal. This paper argues that retail experiences are a significant pillar for retail value, and it introduces a layer framework for experience design in retailing. The framework will improve the accessibility of retail experience design for researchers and managers.
Keywords: 650